Honesty in Language in Special Fugitive Scandal: Forensic Linguistic Studies in Broadcasting Talks Indonesia Lawyers Club - Musawir, Muhammad; Amir, Johar; Saleh, Muhammad (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
Forensic linguistics as a branch of linguistics that analyzes and examines language in legal products, legal processes, and legal evidence still needs to be improved in Indonesia, especially the study of language honesty in crime cases. Therefore, it is important to continue the study of forensic linguistics. This study aims to describe the veracity language in the special fugitive scandal. This research is a type of qualitative research with a descriptive qualitative research design that focuses on analyzing the level of veracity in language in the special fugitive scandal using John Olsson’s Statement Analysis in Linguistic (SAL) model. The data of this research are oral data, namely forensic text narratives contained in talk shows about special fugitives. The data source in this research is the Indonesia Lawyers Club (ILC) talk show. The main theory used in this research is the study of forensic linguistics which is specified in John Olsson’s theory of veracity language. The results of this research indicate that veracity in language in special fugitive scandals tends to have a high level of veracity.